A REVIEW OF HELICOBACTER PYLORI INFECTION DISEASES, ANTIBIOTIC RESISTANCE AND DIAGNOSIS - Paul, Bolai; Adimoolam, Senthil; Qureshi, Mohd Javed; Ismail, Nahlah Elkudssiah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the study was designed to assess the mechanisms of antibiotic resistance in Helicobacter pylori, affecting disease by this infection and diagnostic methods which are used to detect H. pylori. Methods: A wide literature search was performed using PubMed, Medline, Cinahl, Embase, Educational Resources Information Center, PsycINFO, Google Scholar, Scopus, and Web of Science, and review of appropriate epidemiologic studies conducted from 1995 to 2017 for studies fully published investigating a contribution between H. pylori infection, antibiotic resistance, and diagnosis of H. pylori infection. Results: H. pylori infection is extremely contributed to the main symptoms and death that is currently affecting 50–75% of the people in the world. It is more affected in developing countries compared to developed countries. These infections are regarded to be the most important reasons for gastric cancer, peptic ulcer, chronic gastritis, duodenal ulcer, mucosa-associated lymphoid tissue lymphomas, and gastric adenocarcinoma. About 90–100% of duodenal ulcers and 60–90% of gastric ulcers were associated with H. pylori infections. At present, antibiotic resistance is a growing problem for the eradication of H. pylori infection; it contains metronidazole, amoxicillin, clarithromycin, and levofloxacin resistance. Diagnosis of H. pylori infection is a crucial part for the better treatment of those diseases. Different types of testing method for H. pylori infection are used including invasive (endoscopic image, histology, rapid urease test, and culture) and non-invasive (urea breath test, stool antigen test, and serological). Conclusion: H. pylori antibiotic resistance is the major contributor to the failure of H. pylori treatment. Appropriate diagnostic method selected in detecting H. pylori antibiotic resistance may lead to reduced treatment failures and less antibiotic resistance.